Tree mortality of a flood-adapted species in response of hydrographic changes caused by an Amazonian river dam - Assahira, Cyro; Piedade, Maria Teresa Fernandez; Trumbore, Susan Elizabeth; Wittmann, Florian Karl; Cintra, Bruno Bar?ante Ladvocat; Batista, Eliane Silva; Resende, Angélica Faria de; Schöngart, Jochen (Forest Ecology and Management, 2017)
The annual and regular flood pulse is the main hydrologic feature found in the large floodplains along Amazonian rivers triggering nutrient cycles, growth rhythms and life cycles of the biota as well as primary and secondary productivity. The construction of hydroelectric dams in the Amazon basin substantially alters the hydrologic regime resulting in severe social, ecological and environmental impacts. While the majority of studies evaluate these impacts in the area of the reservoir and the surroundings of the dam, we focus on disturbances in floodplain forests downstream of the hydroelectric power plant, in this case the Balbina dam, constructed in the 1980s damming the Uatumã River (Central Amazonia). The lowest topographies in the floodplain forests downstream of the dam are dominated by dead trees of Macrolobium acaciifolium (Benth.) Benth. (Fabaceae), a flood-tolerant species forming annual tree rings in consequence of the flood pulse. In this study we evidence alterations in the magnitude and frequency of the hydrologic conditions of the Uatumã River downstream of the hydroelectric power plant comparing the pre-dam (1973–1982) and post-dam (1991–2012) period analyzing a set of biologically relevant hydrologic indicators. To investigate the relationship between the hydrologic changes caused by the dam and the year of death of individuals of M. acaciifolium we use cross-dating techniques (dendrochronology) and radiocarbon dating (14C) as two independent methods. Cross sections of 17 dead individuals were analyzed and individual tree-ring series cross-dated with a well-replicated living trees’ chronology of the same species and region (1804–2012). The outermost tree ring was isolated to perform radiocarbon dating. The dendrochronological and 14C proxies matched in 88% of the cases, while in the 12% mismatched maximum deviation at least one year. Trees died during periods of consecutive years of inundation, up to two decades after the implementation of the hydroelectric dam. Considering the planning of construction of several dozen dams in the Amazon region there is a critical need to include the downstream impacts in all discussions of hydroelectric implementation. © 2017
Keywords: Banks (bodies Of Water); Climatology; Dams; Environmental Impact; Floods; Forestry; Hydroelectric Power; Life Cycle; Reservoirs (water); Rivers; Dendrochronology; Flood Pulse; Hydrographic Changes; Hydrologic Changes; Hydrologic Conditions; Hydrologic Features; Macrolobium Acaciifolium; Radiocarbon Dating; Hydroelectric Power Plants; Biochronology; Biota; Carbon Isotope; Dam; Dendrochronology; Environmental Impact; Flood; Floodplain; Hydroelectric Power Plant; Legume; Life Cycle; Mortality; Nutrient Cycling; Radiocarbon Dating; Reservoir; Reservoir Flooding; River Basin; Tree Ring; Dams; Floods; Hydroelectric Power; Hydrography; Mortality; Nutrients; Power Plants; Trees; Amazon Basin; Amazonas; Amazonia; Balbina Reservoir; Fabaceae; Macrolobium Acaciifolium